Impact of pulmonary hypertension in patients with acute exacerbation of chronic obstructive pulmonary disease and its effect on healthcare utilization. (1st September 2021) - Munshi, Rezwan F.; Pellegrini, James R.; Patel, Pranavi; Kashin, Maxim; Kang, James; Sexton, Robert; Russe, Jose R.; Makaryus, Amgad N.; Patel, Palakkumar; Thakkar, Samarthkumar; Pelletier, Brandon; Abraham, Tinu; et al.
Abstract : We aim to study the impact of pulmonary hypertension on acutely exacerbated chronic obstructive pulmonary disease (AECOPD). We used the 2016 and 2017 National Readmission Database with an inclusion criterion of AECOPD as a primary and pulmonary hypertension as a secondary diagnosis using ICD 10‐CM codes. Exclusion criteria were age under 18 years, non‐elective admission, and discharge in December. The primary outcome was in‐hospital mortality during the index admission. Secondary outcomes were 30‐day readmission rate, resource utilization, and instrument utilization including intubation, prolonged invasive mechanical ventilation >96 h (PIMV), tracheostomy, chest tube placement, and bronchoscopy during the index admission. A total of 627, 848 patients with AECOPD were included in the study, and 68, 429 (10.90%) patients had a diagnosis of pulmonary hypertension. Pulmonary hypertension was more common among females (61.14%) with a mean age of 71 ± 11.66, Medicare recipients (79.5%), higher Charlson comorbidity index, and treatment in an urban teaching hospital. Pulmonary hypertension was associated with greater mortality (adjusted odds ratio (aOR) 1.89, p < 0.001), higher 30‐day readmission (aOR 1.24, p < 0.001), higher cost (adjusted mean difference (aMD) 2785, p < 0.01), length of stay (aMD 1.09, p < 0.001), and higher instrument utilization including intubation (aOR 199, p < 0.001), PIMV (aOR 2.12, p < 0.001), tracheostomy (aOR 2.1, p < 0.001), bronchoscopy (aOR 1.46, p = 0.007), and chest tube placement (aOR 1.39 p < 0.004). We found that pulmonary hypertension is related to higher in‐hospital mortality, length of stay, increased instrument utilization, readmission, and costs. Our study aims to shed light on the impact of pulmonary hypertension on AECOPD in hopes to improve future management.